PERANAN PAJAK DALAM PENGATURAN EKSPOR HASIL HUTAN - Setiasih Irawanti; Hariyatno Dwiprabowo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1994)
Being concerned with forest resources sustainability due to its extraction speed, Indonesia government tried to restrict forest products export by export bans during 1970s until the midle of 1980s, and by raising of export taxes since the end of 1980s.Export tax is one of government revenue sources. Indonesia government revenue from export tax is relatively small, it only accounts for 0,04% of the total government revenue , or 0,07% of the total revenue out of oil and gas.The more the development of the country, the higher thr governmnet’s revenue from income tax, firm tax, wage tax, and value added tax, and the more the government’s dependency on domestic sources. On the other hand, presently export tax revenue is relatively low. Indonesia government revenue from export tax is important, because the revenue from other taxes is small relatively.The higher the export tax rate, it will impose more restriction of forest products export flow. Statistically, at 99% confidence level, the increase of sawn timber export tax at the end of 1989 has given significant influence on the decrease of sawn timber export volume. Taxation policy is an effective instrument for allocation of forest product resources.Forest product export ban is one of non-tariff barrier, in which repleased by export tax policy is in accordance with GATT agreement. Levying of forest product export tax is a real measures of Indonesia government in executing sustainable development. As a tariff barier, axercising forest product export tax is a real measures of Indonesia government in executing sustainable development. As a tariff barier, exercising forest product export tax is not contrary to the consensus in international trading order.